(untitled) (Scientific journal of the Fergana State University, 2024)
The purpose of this study is to study the legal regulation of legal relations related to the cancellation of adoption, to identify problems in this regard and to develop proposals for improving the legislation and improving the practice of law enforcement. In this article, the foundations of adoption cancellation are analyzed with the help of conceptual, problem-objective, comparative legal, current legal documents and scientific methods of scientific analysis of their application. Annulment of adoption is understood as a legal fact that means annulment of the relationship resulting from adoption in a court of law. As a result of cancellation of adoption, all legal relations between the adopter (his relatives) and the adopted child are terminated. At the same time, mutual rights and obligations between the child and his (biological) parents (his relatives) are restored if they do not conflict with the child’s interests. Therefore, cancellation of adoption is a legal fact that terminates the right and restores the right.